Neuroleptic malignant syndrome with acute renal failure associated with rhabdomyolysis: a case report - Sunakshi Sharma; Sanjay Bhat; Zahoor Ahmed (SpringerOpen, 2024)
Abstract Neuroleptic malignant syndrome is a rare, life-threatening neurologic emergency characterized by fever, rigidity, autonomic instability, mental status changes, and an elevated creatine kinase level. It often occurs shortly after the initiation of neuroleptic treatment, or after a dose increase. The management of patients with NMS is based upon clinical severity and includes supportive care and withdrawal of antipsychotic agents and agents like bromocriptine and dantrolene. Complications include acute renal failure associated with rhabdomyolysis, respiratory failure, electrolyte imbalance, hepatic failure, seizures from hyperthermia, metabolic derangements, etc.